Three Pedagogical Congresses - Jamrożek, Wiesław (Biuletyn Historii Wychowania, 2018)
The paper presents how important for the history of Polish education were: Ogólnopolski Zjazd Oświatowy (the All-Poland Education Convention) in Warsaw (of April 1919) – called the Teachers’ Sejm, the 1st Pedagogical Congress in Poznan and the 4th Pedagogical Congress in Warsaw (of May 1939). The aforementioned convention and both congresses played a significant role in the development of educational thought and practice in interwar Poland. The scope of the issues discussed during sessions was large. It covered issues regarding the school system and the school administration, preschool upbringing and other levels of education including higher education, vocational schools, teachers’ education and teachers’ pragmatics, nonschool education, school and physical education hygiene. Resolutions and motions adopted at Ogólnopolski Zjazd Oświatowy (All-Poland Education Convention) in Warsaw, in April 1919, provided grounds for work on developing a democratic national education system. The main issues of the Congress in Poznan, held on 8–10 July 1929 during the General National Exhibition in Poznan, were referred to also during sessions of consecutive pedagogical congresses organised by the Polish Teachers’ Union: 2nd Pedagogical Congress (in Vilnius, on 4–8 July 1931) and 3rd Pedagogical Congress (in Lvov on 17–21 June 1933). Sessions of the aforementioned 4th Pedagogical Congress in Warsaw were held in May 1939, in special circumstances, when a threat from Hitler’s Germany reached its apogee among the Polish society, including teachers. Resolutions of the 4th Congress included the programme of democratic transformations of the national education system characterised in many aspects even with an explicit social radicalism. They provided broader access to the university education for the youth from farmers’ and workers’ families, develop special schooling and extend the school obligation for blind, deaf, mentally disabled and “morally neglected” children, develop adult education, implement education for primary school teachers only at a university level.